S52 The incidence and impact of viral respiratory infections in adults hospitalized with exacerbations of bronchiectasis. (11th November 2022) - Diggins, B; Prasad, N; Newbern, C; Good, WR; Trenholme, A; Huang, QS; Wong, C
Abstract : Background/Aims: The importance of viral respiratory infections (VRI) in exacerbations of bronchiectasis is poorly understood. However, they have been proposed as the microbiological 'trigger' for bronchiectasis exacerbations. The aims of this study were to describe the rate of VRI in patients hospitalized with bronchiectasis exacerbations and evaluate their effects on exacerbation severity. Methods: Adult patients hospitalised with acute respiratory illness to two hospitals in Auckland, New Zealand between 2012–2015 were screened for inclusion in the Southern Hemisphere Influenza and Vaccine Effectiveness Research and Surveillance (SHIVERS) project, a population-based virus surveillance study. Nasopharyngeal sampling was used to test for respiratory viruses using real-time PCR. Patients with bronchiectasis were identified using ICD-10 code J47, 'bronchiectasis'. Individual patient data and electronic patient records were reviewed; patients with bronchiectasis due to cystic fibrosis were excluded, as were patients with no clinical evidence of bronchiectasis. Pre-specified parameters were used to describe severity of exacerbation. Results: 526 patients with bronchiectasis experienced 979 admissions with acute respiratory illnesses. Nasopharyngeal sampling for VRI was performed in 429 admissions (43.8%). Of these, 154 (35.9%) tested positive for VRI, including 62 (14.4%) cases of influenza, 59 rhinovirus (13.8%) and 20 RSV (4.7%). 11 patients (2.5%) tested positive for more than one respiratory virus. Median LOS was longer for patients with VRI (5 [3–7] vs 4 days [2–6] respectively, p=0.032). Patients with VRI were more likely to receive non-invasive ventilation (3.9% vs. 0.8%, p=0.022), and more likely to have a fever (76% vs. 66%, p=0.034). 4.4% of patients died within 30 days of their first recorded admission, and 16.2% died within a year, with no difference between patients testing positive or negative for VRI. Conclusions: To our knowledge, this is the largest study to investigate the role of viral respiratory infection in patients with bronchiectasis exacerbations. VRI is common in exacerbations requiring hospitalisation and is associated with some markers of more severe illness, including longer duration of hospital admission. Influenza was the most common viral infection, highlighting the importance of public health measures against influenza and other viruses, including vaccination and testing, to limit the effects of viral respiratory infection in bronchiectasis.